2020
DOI: 10.1200/jco.2020.38.4_suppl.427
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of pembrolizumab (pembro) monotherapy versus chemotherapy for PD-L1–positive (CPS ≥10) advanced G/GEJ cancer in the phase II KEYNOTE-059 (cohort 1) and phase III KEYNOTE-061 and KEYNOTE-062 studies.

Abstract: 427 Background: Pts with advanced gastric/gastroesophageal junction (G/GEJ) cancer received pembro monotherapy (200 mg Q3W) 3L+ in cohort 1 of KEYNOTE-059 (NCT02335411), 2L in KEYNOTE-061 (NCT02370498), or 1L in KEYNOTE-062 (NCT02494583). We present efficacy data for patients with PD-L1 combined positive score (CPS) ≥10 tumors in these trials. Methods: In study 059, 46 pts in cohort 1 with PD-L1 CPS ≥10 received pembro. In study 061, 108 pts with PD-L1 CPS ≥10 received pembro (n=53) or chemotherapy (chemo; n=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 0 publications
2
18
0
Order By: Relevance
“…Although the FDA approval of pembrolizumab in chemorefractory gastric and GEJ adenocarcinoma is contingent on positive PD-L1 testing, there are clearly some patients with PD-L1 negative tumors who derive benefit from this agent. PD-L1 positivity using the CPS of 1 was seen in 57.1% of patients in the KEYNOTE-059 study, and the ORR of these patients was 16% (95% CI, [11][12][13][14][15][16][17][18][19][20][21][22][23]. Of note, patients with PD-L1 negative tumors had a 6% ORR (95% CI, 3-13) [15,16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the FDA approval of pembrolizumab in chemorefractory gastric and GEJ adenocarcinoma is contingent on positive PD-L1 testing, there are clearly some patients with PD-L1 negative tumors who derive benefit from this agent. PD-L1 positivity using the CPS of 1 was seen in 57.1% of patients in the KEYNOTE-059 study, and the ORR of these patients was 16% (95% CI, [11][12][13][14][15][16][17][18][19][20][21][22][23]. Of note, patients with PD-L1 negative tumors had a 6% ORR (95% CI, 3-13) [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…The FDA approval stems from the phase II KEYNOTE-059 study (NCT02335411) of pembrolizumab at a dose of 200 mg i.v. every 3 weeks, which showed an overall response rate (ORR) of 12% (95% confidence interval [CI], [8][9][10][11][12][13][14][15][16][17] in all chemorefractory patients, regardless of PD-L1 status, and 16% (95% CI, [11][12][13][14][15][16][17][18][19][20][21][22][23] in patients with PD-L1-positive tumors (57.1% of patients had PD-L1-positive tumors) [15,16]. These response rates are impressive given the chemotherapy-resistant patient population.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, high DKK1 expression was associated with better response to DKN-01 in a study of DKN-01 combined with pembrolizumab in anti-PD-1/PD-L1-inhibitor-naïve advanced gastroesophageal junction and gastric adenocarcinoma. 35 Despite the limited efficacy of adding DKN-01 to gemcitabine/cisplatin in BTC, the safety, PK, PD, and biomarker analyses from this study provided important insights for the development of DKN-01 in this disease. First, safety analyses in 51 patients with advanced BTC demonstrated that the AE profile were consistent with gemcitabine/cisplatin alone.…”
Section: Discussionmentioning
confidence: 88%
“…PFS and ORR were similar between the treatment groups, but responses were more durable in patients who received pembrolizumab than those who received paclitaxel (median duration of response [DOR], 18.0 vs 5.2 months, respectively). Post hoc analyses of patients with CPS ≥10 tumors revealed a greater survival benefit for the pembrolizumab group than the paclitaxel group (HR: 0.64; 95% CI: 0.41-1.02) [23]. In the Phase III KEYNOTE-062 study (NCT02494583), first-line pembrolizumab or pembrolizumab + chemotherapy versus chemotherapy was evaluated in patients with CPS ≥1, HER2-negative, advanced gastric cancer [24].…”
Section: Background and Rationalementioning
confidence: 99%